TYPES OF COMPUTER GRAPHICS AND DESIGN - Akramov Abdurahmon Xaydarali ogli (Scholar Express Journal, 2023)
This article discusses computer graphics and types of design. In the vast realm of technology, computer graphics stands as a vibrant and essential field, shaping the visual experiences of the digital age. From the mesmerizing special effects in movies to the intricate designs of video games, computer graphics have become an integral part of our daily lives.
Keywords: Computer Graphics; Graphic Design; Digital Imaging